Genomic organization, expression and antimicrobial activity of a hepcidin from taimen (Hucho taimen, Pallas). (September 2016) - Wang, Di; Li, Shaowu; Zhao, Jingzhuang; Liu, Hongbai; Lu, Tongyan; Yin, Jiasheng
Abstract: Hepcidin, an antimicrobial peptide, plays a crucial role in innate immune system of teleost fish. As a cysteine-rich peptide, hepcidin possesses a dual function including iron regulation and innate immunity. In the present study, a full-length hepcidin cDNA (HtHep) was cloned and characterized by RT-PCR and RACE techniques from taimen ( Hucho taimen, Pallas), which is a type of rare, precious and cold-water fish species in China. The cDNA contains an open reading frame (ORF) of 267 bp encoding 88 amino acid (aa), with 170 bp located in the 5 ′ untranslated region (UTR) and 151 bp in the 3′ UTR. The genomic sequences analysis showed that the HtHep gene consisted of three exons and two introns (with the length 94 and 251 bp, respectively). With a predicted molecular mass of 2881.4 Da and a theoretical pI of 8.53, the deduced amino acid encodes a signal peptide of 24 aa, prodomain of 39 aa and mature peptide of 25 aa. The signal peptidase (SA-VP) and the motif RX (K/R)R of propeptide convertase suggested the cleavage site of signal and mature peptide. Eight conserved cysteine residues were also identified and formed four disulfide bonds. Pair-wise alignments showed that HtHep clustered together with two fish species of Salmonidae family ( Salmo salar and Oncorhynchus mykiss ) in HAMP1 branch. Quantitative RT-PCR analysis indicated that the mRNA levels of HtHep were detected in a wide range of tissues and the highest level was detected in the liver. Its expression was also detected early during embryonic stage and could be up-regulated in the liver when challenged with pathogenic bacteria ( Yersinia ruckeri ). The recombinant HtHep (rHtHep) had antimicrobial activity against both gram-positive ( Micrococcus lysodeikticus and Staphylococcus aureus ) and gram-negative bacteria ( Escherichia coli ). Our results suggested that HtHep might be involved in the innate immune defense against bacterial pathogens in taimen. Highlights: A hepcidin cDNA (HtHep) was cloned and characterized from Hucho taimen. Genomic organization of HtHep was identified. Expression of HtHep mRNA was detected in a wide range of tissues in Hucho taimen . Expression of HtHep in the liver was up-regulated when challenged with Yersinia ruckeri. rHtHep had antimicrobial activities against several bacterial pathogens.